Low-velocity impact behaviours of sandwiches manufactured from fully carbon fiber composite for different cell types and compression behaviours for different core types - Bozkurt, Ilyas; Kaman, Mete Onur; Albayrak, Mustafa (Walter de Gruyter Gmbh, 2023)
This study aims to manufacture sandwich composite structures consisting of fully fiber-reinforced composites and then to investigate experimentally and numerically the impact and compressive strength and damage mechanisms of these structures for different cell and core types. To achieve this, firstly, composite sandwich plates with triangular, square and rectangular cell structures were manufactured. Low-velocity impact tests were run on sandwich structures with these three different cell geometries and the effect of cell shape on impact strength was determined. Although the maximum contact force of the square structure under impact load was smaller than the maximum contact force of the triangular and rectangular specimens, the specific contact force was 15.52 % greater than the triangular specimen and 16.29 % greater than the rectangular specimen. Then, the specimens with square, egg box and lattice core types were manufactured and compression tests were performed. The specific peak load value for square specimens was 33.2 % greater than that of egg box specimens and 78.1 % greater than that of lattice specimens. In the numerical study, the experimental results were confirmed by applying the progressive failure analysis with the LS-DYNA finite element program.
Keywords: compression test; Hashin failure criteria; low-velocity impact; progressive failure analysis; sandwich structure